Comparative Transcriptome Analysis of Gene Responses of Salt-Tolerant and Salt-Sensitive Watermelon Cultivars’ Roots to Salt Stress - Peng Liu; Chao Gao; Shuai Li; Xudong Wang; Yumei Dong; Chongqi Wang; Zigao Jiao; Jianlei Sun (Plants)
Salt stress, as a significant adverse consequence of global climate change, severely restricts the yield and quality of watermelon. In this study, salt-tolerant cultivar T23 and salt-sensitive cultivar B2 were subjected to a 200 mM NaCl treatment (0 h, 6 h, 24 h, 48 h, and 168 h) at the three-leaf stage, and the adaptation mechanisms of the watermelon roots to salt stress were systematically investigated at the phenotypic, physiological, and gene transcription levels. Phenotypic observations revealed that salt stress inhibited seedling growth, caused leaf curling, and induced root yellowing, with the damage being significantly more severe in B2 than in T23. Compared with B2, the activities of superoxide dismutase (SOD) were increased by −7.13%, 169.15%, 34.95%, 84.87%, and 39.87% under NaCl treatment at 0 h, 6 h, 24 h, 48 h, and 168 h, respectively. Compared to the 0 h NaCl treatment, the proline content in B2 increased by 4.25%, 14.39%, and 110.00% at 24 h, 48 h, and 168 h of NaCl treatment, respectively, while T23 showed increases of 93.74%, 177.55%, and 380.56% at the corresponding time points. The provided physiological data demonstrate that T23 exhibits superior antioxidant and osmoregulatory abilities relative to B2. The transcriptome analysis identified differentially expressed genes (DEGs) between the two cultivars under salt stress, with T23 showing the highest number of DEGs at 6 h, while B2 exhibited a significant increase in DEGs at 168 h. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that metabolic pathways such as plant hormone signal transduction, terpenoid biosynthesis, mitogen-activated protein kinase (MAPK) signaling pathways, transporter activity, and transcription regulator activity play important roles in the salt stress response. Furthermore, yeast overexpression experiments preliminarily validated the critical roles of the tonoplast dicarboxylate transporter gene ClCG01G010280 and the NAC transcription factor gene ClCG05G024110 in salt stress tolerance. This study provides new molecular insights into the salt tolerance mechanism of watermelon and offers potential genetic resources for breeding salt-tolerant varieties.